Pengaruh Pengalaman Kerja dan Ukuran KAP Pada Kualitas Audit dengan Komitmen organisasi Sebagai Pemoderasi - Halifah, Agis Fitriyah; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
This study aims to obtain empirical evidence regarding the effect of work experience and audit firm size on audit quality as well as the moderate influence of organizational commitment. The sample used amounted to 53 respondents with saturated sampling method. Data analysis techniques used are multiple linear regression analysis and moderation regression. The result of multiple linear regression analysis showed that the work experience and audit firm size had a positive effect on the audit quality, while the result of moderation regression analysis showed that the organizational commitment was not able to moderate the influence of work experience on audit quality and organizational commitment to reinforce the influence of the audit firm size on audit quality. Keywords : work experience, audit firm size , organizational commitment, and audit quality.